Principal Sensemaking and Leading School Improvement in Mathematics - Gautreau, David Paul (Université d'Ottawa / University of Ottawa, 2018)
While research has identified the practices that successful school leaders use, the effectiveness of those practices rests on leaders enacting them with great contextual sensitivity. Research literature suggests that leaders should be thoughtful, discerning, careful and dexterous with regard to how they lead. This thesis presents a qualitative, multi-case study of how five elementary school principals lead the improvement of mathematics achievement in their schools. Taking the perspective that leadership is a sensemaking praxis, principals’ perceptions and interpretations of their contexts were explored with the goal of better understanding why they lead the way they do. The evidence revealed that the actions of the principals in this study were the product of their contextually-influenced, idiosyncratic sensemaking. This study demonstrates the value of using the sensemaking praxis perspective as a lens for understanding the enactment of educational leadership. Further, this study has practical implications for principal training, policy implementation, and school improvement.
Keywords: educational leadership; sensemaking; mathematics; praxis; context; enactment; leadership; elementary; school improvement; principal; education